Cultivating Employees Using Maslow's Hierarchy of Needs - Stewart, Carol; Nodoushani, Omid; Stumpf, Jason (Competition Forum, 2018)
Stress caused by climates of fear in the workplace is sapping employee decision-making and causing conflict in the workplace. While hard to quantify, it is easy to understand why intelligent and engaged employees are the ideal: there are fewer mistakes and higher productivity. The primary metric used to frame the reasons for motivation is Maslow's Hierarchy of Needs. It is also vitally important to understand the power balance between employees and employers. By the very nature of employment, employers have less need for a particular employee unlike the employee who cannot afford to be unemployed.
Keywords: Business And Economics; Compensation; Competition; Corporate culture; Emotions; Employees; Employers; Employment; Employment security; Empowerment; Games; Handbooks; Happiness; Job satisfaction; Personal computers; Physiology; Software; Stress; Success; Work environment; Workers; dept.mgt; peer-reviewed

Handbook on household hazardous waste - Cabaniss, Amy (Bernan, 2018)
Household hazardous waste (HHW) is a topic that affects every individual and community given the nearly universal use, storage, and disposal of chemical consumer products. Yet many communities lack the basic information, guidance, and planning support for HHW collection and management so that struggles (e.g., to gain politicians’ and residents’ support, host a collection, build a facility, affect behavior change, and encourage extended producer responsibility) continue on a regular basis. This book is for professionals, students, government officials and others interested in HHW and accommodating the increasing societal demand for this disposal option. In the evolving field of HHW collection and management, this book: provides an unparalleled, comprehensive look at household hazardous wasteis a must-have for anyone interested in the solid waste management field, whether novice or experienced, because of the valuable overview and specifics it provides for addressing the ubiquitous issue of HHWoffers perspectives based on many collective years of experts’ accrued insightthe chapters are written by leading practitioners and visionariesis packed with useful information on many aspects of HHW including its definition, mechanisms for collection and creative collection options, tools for behavior change, and product stewardshipoffers an extensive resource list for more information. Much has changed in 10 years since the first edition appeared, and each chapter in the Handbook on Household Hazardous Waste, Second Edition, is updated to reflect changes and advances in the field of HHW collection and management. This includes updated appendices and the extensive resource list.
Keywords: dept.mgt

Kinship ties and employee theft perceptions in family-owned businesses - O'Brien, Kimberly E; Minjock, Robert; Colarelli, Stephen M; Yang, Chulguen (European Management Journal, 2018)
Family business research typically views family firms using the frameworks developed for non-family businesses (e.g., agency theory, institutional theory). Thus, using an evolutionary perspective on family may help address gaps in the family business literature, particularly regarding deviance. In the current study, we use kin selection theory to predict that family members receive preferential treatment and this history of privileges can create entitlement and lead genetically-related employees to misuse company resources. Using an experimental vignette methodology and data from 161 people recruited from an online panel, we found that the participants' purported genetic relatedness to the owner of a business increased their theft intentions and decreased their expected severity of sanctions and likelihood of being reported. Biological sex moderated the relationships between genetic relatedness and theft intentions, as well as between expectations of punishment and theft intentions. Specifically, when females expected higher severity of sanctions or likelihood of whistleblowing, they were less likely to report theft intentions, compared to males. The results of this study suggest that family business owners should protect against theft by all employees, including genetic relatives. Future research using field samples would help provide context for these findings. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Counterproductive behaviors; Evolutionary theory; Family business; Kinship; Lab experiment; Nepotism; Theft; dept.mgt; peer-reviewed

Making sense of mindfulness in management education - Yang, Charlie (Developing a Sustainability Mindset in Management Education, 2018)
Keywords: dept.mgt

Pay openness movement: Is it merited? Does it influence more desirable employee outcomes than pay secrecy? - Marasi, Shelly; Wall, Alison; Bennett, Rebecca J. (Organization Management Journal, 2018)
Organizations are currently moving toward increased pay openness in the workplace; thus, it is important to determine the influence pay communication practices (pay secrecy and pay openness) have on employee outcomes and whether the increase in pay openness is merited and more beneficial for organizations. The purpose of this article is to analyze pay communication’s influence on workplace deviance and organizational citizenship behaviors (OCBs). Specifically, pay secrecy practices are hypothesized to influence employees to engage in less OCBs and more workplace deviance. Informational justice and distributive justice perceptions are included as mediators. Pay secrecy leads to greater workplace deviance as well as less OCBs and justice perceptions and thus, inferring the pay openness movement is merited. A Pay Communication scale was developed and validated for this study. Practical implications, limitations, and future research directions are provided. © 2018 Eastern Academy of Management.
Keywords: dept.mgt; distributive justice; informational justice; organizational citizenship behaviors; pay communication; pay openness; pay secrecy; peer-reviewed; workplace deviance